2009
DOI: 10.1007/s11595-009-1137-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization of F-doped silica glass

Abstract: Pure and fluorine-doped silica glass were fabricated by plasma chemical vapour deposition (PCVD) and characterized using Raman and infrared spectrum. The change in Raman intensity of 945 cm -1 peak, relating to ≡Si-F stretching vibration, agrees with the change of F content. Compared with measured wavenumber in IR spectrum, the calculated absorption wavelength confirms the incorporation form of F into the glass, the detail of which is a tetrahedron with a Si atom in the center coupled with one F atom and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…We next questioned how anodization time affected the pSi surface chemistry. Figure presents typical anodization time-dependent IR absorbance spectra across the Si–F 3 , O y –Si–F ( y = 1–3), and Si–O–Si (950–1200 cm –1 ) (panel A) and SiH x ( x = 1–3) and O y –SiH ( y = 1–3) (2000–2300 cm –1 ) (panel B) spectral regions. The Si–F 3 /O y –Si–F/Si–O–Si IR spectral region (Figure A) shows that the Si–O–Si absorbance remains relatively constant, and there is little detectable Si–F 3 /O y –Si–F species until the anodization time reaches and exceeds 300 s. The O y –Si–F ( y = 1–3) and Si–F 3 species are very prominent when pSi has been etched for 600 s. The presence of Si–F 3 and O y –Si–F at longer anodization times arises from HF stoichiometric limitations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next questioned how anodization time affected the pSi surface chemistry. Figure presents typical anodization time-dependent IR absorbance spectra across the Si–F 3 , O y –Si–F ( y = 1–3), and Si–O–Si (950–1200 cm –1 ) (panel A) and SiH x ( x = 1–3) and O y –SiH ( y = 1–3) (2000–2300 cm –1 ) (panel B) spectral regions. The Si–F 3 /O y –Si–F/Si–O–Si IR spectral region (Figure A) shows that the Si–O–Si absorbance remains relatively constant, and there is little detectable Si–F 3 /O y –Si–F species until the anodization time reaches and exceeds 300 s. The O y –Si–F ( y = 1–3) and Si–F 3 species are very prominent when pSi has been etched for 600 s. The presence of Si–F 3 and O y –Si–F at longer anodization times arises from HF stoichiometric limitations …”
Section: Resultsmentioning
confidence: 99%
“…Figure presents typical anodization time-dependent IR absorbance spectra across the Si–F 3 , O y –Si–F ( y = 1–3), and Si–O–Si (950–1200 cm –1 ) (panel A) and SiH x ( x = 1–3) and O y –SiH ( y = 1–3) (2000–2300 cm –1 ) (panel B) spectral regions. The Si–F 3 /O y –Si–F/Si–O–Si IR spectral region (Figure A) shows that the Si–O–Si absorbance remains relatively constant, and there is little detectable Si–F 3 /O y –Si–F species until the anodization time reaches and exceeds 300 s. The O y –Si–F ( y = 1–3) and Si–F 3 species are very prominent when pSi has been etched for 600 s. The presence of Si–F 3 and O y –Si–F at longer anodization times arises from HF stoichiometric limitations Figure B shows that the silane absorbance increases with increasing anodization time, as one would expect for a layer of pSi that is increasing in thickness; however, oxidized silane species are also clearly observed when pSi has been etched for 600 s. At 600 s anodization times, HF is no longer present and reaction of Si–F 3 and SiH x ( x = 1–3) species with water to form O y –Si–F ( y = 1–3) and O y –SiH ( y = 1–3), respectively, becomes the dominant pathway …”
Section: Resultsmentioning
confidence: 99%
“…Due to the coarse grains and serious mixed crystals of heavy cylinder after rolling, the tedious process of heat treatment must be done after rolling. Studies have shown that improve the cooling of heavy cylinder after rolling can help the grain to become uniform and refinement [2]. Although the existing heat treatment process can make the grain refinement to a certain extent, the use of air cold after rolling and the performance heat treatment using copious cooling lead to a low cooling rate of the center part, and the mechanical properties cannot be further improved [3].…”
Section: Introductionmentioning
confidence: 99%